Immunofluorescent Detection of Intraerythrocytic Bartonella henselae in Naturally Infected Cats - Rolain, J. M. (American Society for Microbiology, 2001)
To determine the presence of Bartonella henselae bacteremia in six cats, we compared isolation using blood culture with direct immunofluorescence on blood smears. Three cats that were positive by blood culture were also positive by direct immunofluorescence, and laser confocal microscopy confirmed the intraerythrocytic location of B. henselae.